FROM LANGUAGE TO NATION: STEPAN KOZHUMIAKA IS A FIGHTER FOR THE LANGUAGE RIGHTS OF THE UKRAINAIN PEOPLE - Колісник, Юрій (Linguistic Bulletin (Movoznavchyi Visnyk), 2019)
Under the conditions of building up the Ukrainian state the problem of the Ukrainian language functioning is gaining more and more significance in different spheres of the political, economical and cultural life. In spite of the citizens’ patriotic set, due to the inertial manifestations in the state humanitarian policy the Ukrainian language has not got the necessary evaluation, though discussions concerning its status are still being provided. Struggle for the Ukrainian language has a big 116 terrible history – starting form the first protests in XVII c. against the prohibition of conducting liturgies in the native language, russification of the primary education; people’ actions against Valuyev’s directive and Emsk decree in the second half of the XIX c.; protest suicides of M. Skrypnyk, M. Khvyliovyi (1933), O. Hirnyk (1978) against violent russification up to the accusing work by I. Dziuba «Internationalism or russification?» (1965), deprecation of the imposing Russian in schools, higher educational establishments and other official organizations and institutions on behalf of the representatives of the Ukrainian Helsinki Group, Narodnyi Rukh, creative intelligence in 70s, 80s, 90s of the XX c. and up to the newest appeals of the educators, educationalists, artists, politicians Larysa Masenko, Lina Kostenko, Iryna Farion, Larysa Nitsoy, Pavlo Movchan, Dmytro Kapranov, Mykola Tomenko, Ivan Malkovych. Among the bright representatives of the Ukrainian people who have struggled for the language-culture rights during different historical periods an important place is occupied by the outstanding philologist, dissident, engineer-road-maker Stepan Kozhumiaka from Novomyrhorod. The purpose. The article is fixed on the role of the Ukrainian philologist, sociologist, engineer-roadmaker, Soviet political prisoner Stepan Kozhumiaka in the struggle for the language-cultural rights of the Ukrainians under the conditions of the communist system and wakening the citizens’ national consciousness on the examples of his epistolary heritage. General pondering of the achievements and faults of the public movement for preservation the native language will contribute to the solution of the wide range issues which are gaining great actuality under the conditions of the building up the Ukrainian state. Due to this research of the struggle for keeping and functioning the Ukrainian language is a very important task nowadays. Results. The article vividly shows the state of functioning the Ukrainian language in the USSR in 60s-70s XX c. Though much spoken nowadays, the negative tendencies in the Ukrainian language-culture situation are still being kept. It is shown by the comparative analysis of the past and present ideas. Originality. The Ukrainian language has not yet been thoroughly explored by means of the letters by the famous representative of the Ukrainian dissidents Stepan Kozhumiaka. The article is the first attempt to do this. Conclusion. Party-Soviet management of the USSR, continuing the long lasting policy of the tsar Russia, made numerous measures aimed at imposing Russian in the pre-school, middle and high education, which led to the tragic consequences in the language situation in Ukraine. Having comprised the spiritual life of the Ukrainian society, the total Russian dominance made a great damage to the Ukrainian culture and became the primary cause of the Ukrainian people’s assimilation, degradation of its public consciousness and decline of the national dignity. Imposing Russian in the humanitarian sphere was carried out by extracting the names of the outstanding figures of our people who had enriched the Ukrainian culture and the bright events from the Ukraine’s history out of the scientific, literature and arts works. The policy of imposing Russian caused protests in different layers of the Ukrainian society. The representatives of the dissident movement tried to prevent from the further Russian dominance of the Ukrainian people and to revive the Ukrainian language, culture, spirituality. Their activity in struggling for national rights of the Ukrainian people should be an example in present days.